A novel photochromic metal–organic framework with good anion and amine sensing. Issue 19 (23rd April 2019) - Li, Xiao-Nan; Li, Li; Wang, Hai-Yu; Fu, Chen; Fu, Jia-Wei; Sun, Ya-Nan; Zhang, Hong
Abstract : The framework exhibits photochromism and high sensitivity of amines and Cr2 O7 2−, and it also can be used as test strips. Abstract : A novel metal–organic hybrid photochromic compound [Zn (CV) (L2)]·2H2 O (1 ) (CV = N, N ′-4, 4′-bipyridiniodipropionate, H2 L2 = isophthalic acid) has been synthesized solvothermally. Compound1 features a two-dimensional (2D) framework structure, exhibiting photochromic properties under sunlight and UV irradiation with an obvious color change from colorless to dark blue. Meanwhile, the luminescence properties of1 were investigated, and the results suggested that1 has good properties of detecting dichromate ions. Furthermore, compound1 shows different color changes when exposed to different alkyl-amines, and1 can also be deposited into paper to use as portable test strips. This work can be applied to practical applications as a multifunctional detector against light and chemicals.